A Teoria Gerativa nos estudos de aquisição do português brasileiro (Revista de Estudos da Linguagem, 2003)
The aim of this paper is to present some of the studies on theacquisition of Brazilian Portuguese as a first language, which havebeen published in the last few years in our country, making use ofthe generative grammar theory in their analysis of the child´s speechdata. The topics that have been analysed are the systems: D, IP, CP,and complementation/adjunction in complex sentences. Additionalresearch on the acquisition of Brazilian Portuguese as a secondlanguage is also shown. The studies briefly discussed here cancontribute to prove the relevance of the generative theory in thedevelopment of the Language Acquisition area.